Los periódicos ambientales y su incidencia en el aprendizaje de las ciencias naturales de los estudiantes del 5º año de educaciòn básica paralelo “d” de la Unidad Educativa Fiscal Mixta Alfredo Noboa Montenegro cantón Caluma provincia Bolívar, en el período 2011 - Cobos Verdezoto, Marcia Marisol (2011)
Implementation of school newspapers with ads of Environmental Activities at the level of learning with students from Year 5 General Education Basic parallel "D" in the field of Natural Sciences of La Unidad Educativa Fiscal Joint Alfredo Noboa Montenegro Canton Caluma Bolivar Province in the previous 2011, prepared by the students.; Cobos and Espin Verdezoto Marcia Marisol Lucia Pozo Belgium, before obtaining a degree in Science Education, Philosophical and Humanistic, mention Basic Education Guaranda City, Province Bolivar The problem arises when students discover that the base year in question, neglecting to treat subjects with environmental activities and, therefore are not recognized as an integral part of the environment and their interrelationships, so there is poor conservation actions natural and social environment, disadvantaging their overall development, and that there will be a positive change in lifestyle, so it is necessary to develop an innovative approach as a strategy to help us raise awareness in all its aspects. Therefore school newspapers are a media application drafted, developed and produced by students of a school, they help to develop intelligence, because as students are analyzing and synthesizing environmental issues ads are internalized principles values, laws that strengthen our learning process through which they acquire new abilities, skills, knowledge, behaviors, or values as a result of the study, experience, training, reasoning and observation. We propose a general and three specific target them to pick up the object and purpose of our project as is knowing the incidence of school newspapers with notice of environmental activities at the level of learning. One hypothesis which raises a clear question "have a positive impact the completion of design and construction of school newspapers with ads of environmental activities at the level of learning in students?. It has been tested with highly satisfactory results in levels, as it is subject to the results that have been derived by applying the survey through questionnaires answered by students, along with the working guide for the design and construction the school newspaper with environmental ads, XIV applying this result has given us a proposal for the innovative teaching design theme is a methodological guide for building and presenting school newspapers with ads of environmental activities at the level of learning, which develops and consolidates learning meaningful and functional. On the basis of research and active participation of students who produce their newspapers with ads of environmental activities with love and enthusiasm, developing values to care and preserve the nature or environment that is their home. Also apply to students from 5 the year of EGB parallel "D" a survey of ten questions related to the variables set in this project so that within its own structure to give their ideas, broaden and discuss them, and through participatory methodologies new and innovative strategies that actively enable the student to be the builder and generator of new knowledge, relevant, meaningful and functional. On such a basis we used primary techniques which we have taken the test observation and consolidate results as solid base that will lead to conclusions such as: Environmental Education is in the transverse axis of education where students design and build their school newspaper with ads of environmental activities that improve their intellectual, emotional and motor driving changes in their quality of life because it presents the proposal Methodological guide to shops school newpaper with ads of enviroramental activities to improve the level of learning